Gleichwertige Lebensverhältnisse - ein Messkonzept regionaler Lebensverhältnisse - Elke Dahlbeck; Franz Flögel; Antonia Milbert; Marc Neu (Institut Arbeit und Technik (IAT), 2022)
Many measurement concepts of equal living conditions fail to meet central scientific requirements. A comparison and assessment of the equivalence of living conditions has therefore been difficult up to now. This paper presents a newly developed measurement concept that addresses the most frequent points of criticism. A two-stage measurement concept is proposed. In a first step, the regions are grouped into seven types of areas based on the dimensions "social situation", "economic intensity" and "population development/age structure". In a second stage, these types of areas can be used to better analyse and evaluate more specific indicators or further dimensions of equal living conditions with regard to their effect on socially disadvantaged and/or elderly people. This two-stage approach allows the indicators of the second stage to be considered at the appropriate spatial level of detail, i.e. at the raster, municipality, district or functional spatial level. Examples of this are shown. The interpretation and evaluation of these indicators in terms of equal living conditions were validated through workshops and interviews in three case studies, the city of Gelsenkirchen and the districts of Dithmarschen and Mansfeld-Südharz. The article concludes with an outlook on upcoming steps for further development with regard to continuous monitoring on the basis of this measurement concept.
Keywords: 330; Armut; accessibility; Chancengleichheit; Daseinsvorsorge; Gerechtigkeit; Grundversorgung; gleichwertige Lebensverhältnisse; regionale Ungleichheit; demografischer Wandel; Wohlstand